Asumiendo la vida con una taza de café - Chávez Achong, Julio (2022)
Coffee growing occupies a significant place in the global and national economy and agricultural production, but also in the socioecosystems where it is located, which in the case of Peru is mainly the upper Amazon. Little thought is given to this last characteristic. This text does not present the results of an empirical research. It intends to be an essay based on approaches and concepts of diverse sciences, highlighting the natural and sociocultural articulation in coffee growing activities. It pretends to make visible co-evolutionary lines between nature and human society that may predispose us to be more sensitive and more responsible with their future.